Determinants of hand-hygiene practices in India: reflections from the 76th round National Sample Survey, 2018. (14th October 2021) - Biswas, Sonali Smriti; Karmakar, Ranjan
Abstract: This paper studies the differences and determinants of handwashing practices in India and identifies sections of the population with poor handwashing practices who are relatively more vulnerable during the COVID-19 pandemic. We have used the data from the recent National Sample Survey (NSS, 76th round) for India (2018). Bivariate and logistic regression analyses have been performed to predict the determinants of handwashing practices across states and socio-economic groups. Levels of education of the household head, Usual Monthly Per Capita Expenditure (UMPCE) of the household, access to water (other than drinking water) resources and sanitation facilities, and the availability of water with soap in and around latrines are major socio-economic and demographic factors that impact handwashing practices. Higher access to principal sources of water for drinking and other purposes, access to bathrooms and latrines with soap, and the availability of water in or around latrines increase the likelihood of handwashing among the people. Universal handwashing across different sections of the population will be effective to prevent further infection. The available data help us to identify the vulnerable sections of the population which are towards the lower end of the handwashing compliance spectrum. The policymakers can outline specific planning and strategy implementation for them. HIGHLIGHTS: The National Sample Survey is a recent assessment of sanitation and hand-hygiene practices in India. It gives a regional- as well as community-level picture of handwashing practices. It provides a detailed account of the determinants of hand-hygiene practices. This survey is relevant in the current situation of the COVID-19 pandemic. It fulfils the gaps in the research of access to water resources and related hand-hygiene practices.